A Prospective Clinical Trial Comparing Visible Light Spectroscopy to Handheld Doppler for Postoperative Free Tissue Transfer Monitoring. Issue 3 (September 2017) - Mericli, Alexander F.; Wren, James; Garvey, Patrick B.; Liu, Jun; Butler, Charles E.; Selber, Jesse C.
Abstract : Background: Early detection of compromised free flap perfusion is critical. A common modality of thrombosis detection, physical examination augmented with hand-held Doppler, provides only intermittent data and is insensitive to venous compromise. Visible light spectroscopy provides continuous, noninvasive evaluation of tissue perfusion. The authors hypothesized that visible light spectroscopy is a more sensitive and specific monitoring method for early detection of postoperative flap compromise than intermittent hand-held Doppler and clinical examination. Methods: The authors prospectively conducted a controlled study evaluating the sensitivity, specificity, and accuracy of the T-Stat Model 303 VLS oximeter versus that of intermittent Doppler and clinical examination. The authors prospectively collected and analyzed patient data, complications, reoperations, flap failures, and tissue oxygen saturation. Results: Sixty-eight patients with 81 flaps completed the study. The majority of flaps (86.4 percent) were either transverse rectus abdominis musculocutaneous or deep inferior epigastric artery perforator flaps. The mean tissue oxygen saturation for all flaps in the study was 56.7 ± 7.1 percent (range, 39.4 to 72.1 percent) and did not differ significantly with patient comorbidity or flap type. During the course of the study, three flaps were returned to the operating room for exploration because of a perfusion abnormality, and the resulting salvage rate was 100 percent. The sensitivity, specificity, and accuracy of visible light spectroscopy were found to be greater than both intermittent Doppler and clinical examination. Conclusion: Visible light spectroscopy is a reliable, continuous adjunct to free tissue transfer monitoring with advantages over intermittent hand-held Doppler and clinical examination. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, II.